Letter from James B. Guthrie to James Curtis Booth, March 21, 1855 - Guthrie, James (1855)
James B. Guthrie (1792 - 1869), United States Secretary of the Treasury from 1853-1857, writes to James Curtis Booth (1810-1888) concerning authorization to ship quantities of fusible alloys to Pittsburgh, Cincinnati and Monroe. Guthrie's signature has been cut away.
Keywords: Guthrie, James, 1792-1869; Booth, James Curtis, 1810-1888; United States. Department of the Treasury; United States Mint; Mint of the United States